Evaluation of Glutamine Utilization in Patients With Sickle Cell Disease. Issue 1 (8th January 2023) - Wu, Han-Wei; Gannon, Michael; Hsu, Lewis L.
Abstract : Glutamine (Gln) was FDA-approved in 2017 to reduce acute sickle cell disease (SCD) pain and acute chest syndrome. However, typical pediatric patients with SCD exhibit moderate adherence, measured by a medication possession ratio <80%. This study examined Gln utilization in a "real-world" clinical setting to determine factors influencing medication adherence and to characterize the impact of an interdisciplinary team approach at an institution with specialty pharmacy services. A retrospective chart review identified 40 patients prescribed Gln by sickle cell specialists over a 2-year period and met selection criteria. Gln medication possession ratio for pediatric (72%) and adult (76%) patients were higher than other SCD medications. Pediatric patients (74%) demonstrated significantly lower first-attempt insurance approval rate compared with adult patients (95%) ( P =0.0026), suggesting an initial access barrier for pediatric patients. Pediatric patients demonstrated significantly higher number of medication fills (9.11 fills) compared with adult patients (3.86 fills) ( P =0.007), which suggests interdisciplinary collaboration may facilitate sustainable management of a new therapy. The majority of pediatric (89%) and adult (90%) patients reported high satisfaction with Gln ("excellent") with minor or no side effects. Multidisciplinary health care provider collaborations and tracking medication adherence metrics can help address barriers to care for SCD patients.